2000
DOI: 10.1159/000055641
|View full text |Cite
|
Sign up to set email alerts
|

Tear Nitrite and Nitrate Levels as Nitric Oxide End Products in Patients with Behçet’s Disease and Non-Behçet’s Uveitis

Abstract: To evaluate the role of nitric oxide (NO) in ocular inflammation, tear nitrite and nitrates (NN) as NO end products were determined in 11 patients with Behçet’s disease (BD) and in 11 with non-Behçet’s uveitis (NBU) during the active and remission stages and in 12 healthy controls. Median (with the range) NN levels were 82.29 (59.60–98.25) µmol/l in the active and 98.25 (52.88–246.92) µmol/l in the remission stage of BD; 88.17 (25.99–116.73) µmol/l in the active and 83.00 (31.04–250.28) µmol/l in the remission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Other researchers have described the opposite and argued that decreased NO levels in the active stage might be attributable to the rapid transformation of NO to peroxynitrites [31,32]. When analyses were done according to the clinical features, a significant difference was observed in patients with skin lesions.…”
Section: Discussionmentioning
confidence: 96%
“…Other researchers have described the opposite and argued that decreased NO levels in the active stage might be attributable to the rapid transformation of NO to peroxynitrites [31,32]. When analyses were done according to the clinical features, a significant difference was observed in patients with skin lesions.…”
Section: Discussionmentioning
confidence: 96%
“…In the eye, there is a similar exocrine gland, the lacrimal gland, which produces important tear components to help protect ocular surfaces. It has been reported that human tears contain relatively high concentrations of nitrate 20-109 μM 31,32 and we hypothesized that lacrimal glands would have similar functions to salivary glands in nitrate metabolism. Our results from porcine tissues show that the lacrimal gland itself contains the most nitrate (234 ± 101 nmol/g) compared to other organs examined, including salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Yilmaz et al demonstrated that the patients who received the treatment of Behçet uveitis had the elevated levels of NO in the aqueous humor (21). A study by Mirza et al with a small number of patients with BD (6 patients) showed that the tear nitrate/nitrite levels were decreased in the active group (6 patients) (17). However, our study demonstrated opposite results, and we think that the sample size of that study was quite small when compared with that of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some experimental studies suggest that NO may play a role in the pathogenesis of endotoxin-induced uveitis (EIU) as a proinflammatory mediator and that increased NO production may lead to hemodynamic and vascular permeability changes (8)(9)(10)(11)(12)(13). Although several studies (14-16) have investigated the blood NO levels in patients with BD, to our knowledge, there is only one study (17) that assessed the tear NO levels of those patients. Therefore, the aim of our study was to evaluate the tear nitrate/nitrite levels as NO end products in patients with BD in comparison with those of healthy subjects.…”
Section: Introductionmentioning
confidence: 99%